An isochronic substitution benefit study of the effects of screen time on the cognitive abilities of 3–6 children - Zhenya, Chang; Aifeng, Zhu; Ling, Wang (Frontiers in Psychology, 2024)
Purpose: To investigate the impact of substituting screen time with other activities on children's cognitive ability. Method: A total of 583 children (299 males and 284 females), aged 3-6 years, were selected as participants.Correlation, regression, and isochronic substitution analyses were used.Results: Screen entertainment time on TV (SET_TV) was negatively associated with children's math ability. However, screen learning time on other electronic devices besides TV (SLT_OED) and non-screen learning time by learning alone (NSLT_LA) were positively associated with math ability and language ability. After controlling for gender, age, and family socio-economic status, SET_TV remained negatively associated with math ability, while NSLT_LA remained positively correlated. Furthermore, substituting 10 minutes of SET_TV with NSLT_LA resulted in an increase of 0.55 in language ability and 0.87 in math ability.Similarly, substituting SLT_OED, sleeping at home, and exercising outside of kindergarten for 10 minutes of SET_TV resulted in an increase of 0.90, 0.43, and 0.61 in math ability, respectively. Conclusions: There are cognitive benefits when screen recreation time is replaced with screen learning time, non-screen learning time, sleep time, and exercise time, with the highest benefits observed when screen recreation time is substituted with NSLT_LA.